2009
DOI: 10.1051/0004-6361/200912543
|View full text |Cite
|
Sign up to set email alerts
|

The YORP effect on 25 143 Itokawa

Abstract: Context. The asteroid 25143 Itokawa is one of the candidates for the detection of the Yarkovsky-O'Keefe-Radzievskii-Paddack (YORP) effect in the rotation period. Previous studies were carried out up to the 196 608 facets triangulation model and were not able to provide a good theoretical estimate of this effect, raising questions about the influence of the mesh resolution and the centre of mass location on the evolution the rotation period. Aims. The YORP effect on Itokawa is computed for different topography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 30 publications
9
62
1
Order By: Relevance
“…YORP spin-down). In particular, studies based on the Hayabusa-derived shape models predicted rotational accelerations (Scheeres et al 2007;Breiter, et al 2009) of (-5.5 to -2.0) × 10 −7 rad day −2 , which differ significantly from our observed value of 3.54 × 10 −8 rad day −2 . These predictions were also inconsistent with an upper limit of |ν| < 1.5 × 10 −7 rad day −2 that was derived from existing light-curve observations in 2008 (Ďurech et al 2008b).…”
Section: Thermophysical Analysis and Measured Density Inhomogeneitycontrasting
confidence: 99%
See 3 more Smart Citations
“…YORP spin-down). In particular, studies based on the Hayabusa-derived shape models predicted rotational accelerations (Scheeres et al 2007;Breiter, et al 2009) of (-5.5 to -2.0) × 10 −7 rad day −2 , which differ significantly from our observed value of 3.54 × 10 −8 rad day −2 . These predictions were also inconsistent with an upper limit of |ν| < 1.5 × 10 −7 rad day −2 that was derived from existing light-curve observations in 2008 (Ďurech et al 2008b).…”
Section: Thermophysical Analysis and Measured Density Inhomogeneitycontrasting
confidence: 99%
“…Assuming a moment of inertia, I Z , of 7.77 × 10 14 kg m 2 (Breiter et al 2009) along with a moderately rough surface at cm scales (Ostro et al 2004;Müller et al 2005) with a uniform spatial distribution, the ATPM predicts a rotational acceleration of -1.80 × 10 −7 rad day −2 , consistent with previous determinations. A COM shift can reconcile our YORP model with the observed value, which we can determine by combining the ATPM with the methodology used for calculating such COM offsets (Scheeres & Gaskell 2008).…”
Section: Thermophysical Analysis and Measured Density Inhomogeneitysupporting
confidence: 81%
See 2 more Smart Citations
“…Especially when previous studies have shown that the YORP effect can be highly sensitive to unresolved shape features and surface roughness (Statler 2009;Rozitis & Green 2012), the shape model resolution (Breiter et al 2009), and internal bulk density distribution (Scheeres & Gaskell 2008;Lowry et al 2014). However, Geographos has a relatively high YORPcoefficient of 0.01 (see Rossi et al 2009or Rozitis & Green 2013b for a definition), and Rozitis & Green (2013a) showed that asteroids with high values are less sensitive to the inclusion of concavities in their global shape model.…”
Section: Modelling Critiquesmentioning
confidence: 99%